Characteristics of physical progression in martial arts - Tkachuk, M. G.; Levitskiy, A. G.; Rudenko, G. V.; Simakov, A. M. (Theory and Practice of Physical Culture, 2025)
Objective of the study was to contrast the physical growth metrics of athletes who practice judo and taekwondo.